Clethra fimbriata hexanic extract triggers alteration in the energy metabolism in epimastigotes of Trypanosoma cruzi - Pardo-Rodriguez, Daniel; Lasso, Paola; Santamaría-Torres, Mary; Cala, Mónica P.; Puerta, Concepción J.; Méndez Arteaga, Jonh Jairo; Robles, Jorge; Cuervo, Claudia (Frontiers in Molecular Biosciences, 2023)
Chagas disease (ChD), caused by Trypanosoma cruzi, is endemic in American countries and an estimated 8 million people worldwide are chronically infected. Currently, only two drugs are available for therapeutic use against T. cruzi and their use is controversial due to several disadvantages associated with side effects and low compliance with treatment. Therefore, there is a need to search for new tripanocidal agents. Natural products have been considered a potential innovative source of effective and selective agents for drug development to treat T. cruzi infection. Recently, our research group showed that hexanic extract from Clethra fimbriata (CFHEX) exhibits anti-parasitic activity against all stages of T. cruzi parasite, being apoptosis the main cell death mechanism in both epimastigotes and trypomastigotes stages. With the aim of deepening the understanding of the mechanisms of death induced by CFHEX, the metabolic alterations elicited after treatment using a multiplatform metabolomics analysis (RP/HILIC-LC-QTOF-MS and GC-QTOF-MS) were performed. A total of 154 altered compounds were found significant in the treated parasites corresponding to amino acids (Arginine, threonine, cysteine, methionine, glycine, valine, proline, isoleucine, alanine, leucine, glutamic acid, and serine), fatty acids (stearic acid), glycerophospholipids (phosphatidylcholine, phosphatidylethanolamine and phosphatidylserine), sulfur compounds (trypanothione) and carboxylic acids (pyruvate and phosphoenolpyruvate). The most affected metabolic pathways were mainly related to energy metabolism, which was found to be decrease duringThis is a provisional file, not the final typeset article the evaluated treatment time. Further, exogenous compounds of the triterpene type (betulinic, ursolic and pomolic acid) previously described in C. fimbriata were found inside the treated parasites. Our findings suggest that triterpene-type compounds may contribute to the activity of CFHEX by altering essential processes in the parasite.